Mild cognitive impairment: a review and nursing implications. - Hodson R; Keady J (British Journal of Nursing, 2008)
The concept and classification of 'mild cognitive impairment' is disputed territory. This article reviews the literature on mild cognitive impairment and suggests that despite the complexity, early identification of dementia presents an ideal opportunity for nurses to work together with other statutory and voluntary partners, to provide support and intervention for people living with this stage of the condition and their families. Practice that is evidenced through individual and family history, coupled with a range of psychosocial interventions, including a quality-of-life appraisal, would seem an ideal way to structure support at this transitional point in time. A fictitious case study is included which demonstrates that stress and negative adjustment are just as likely to occur early in the course of dementia as later on in the condition.